Post-mortem analysis of silica bricks for coke ovens - Camerucci, Maria Andrea (2006)
Silica bricks that operated during 12 and 25 years in coke ovens at pusher and coke chamber zones were studied. Two different regions of the bricks were analysed: that in contact with coal (oven side) and the other in contact with burners (burner side). Unused silica bricks were also studied as reference. The evolution of the phases was accomplished by X-ray diffraction qualitative analysis. The method of standard additions or spiking method was employed in order to do an estimation of the residual quartz content. The picnometric densities of silica bricks were determined on powder samples in kerosene. The bricks were also characterized by bulk density and apparent porosity measurements on the basis of DIN EN 993-1 standard. The study of the microstructural evolution was carried out by optical microscopy. The cold crushing strength (CCS) was determined at room temperature according to DIN 51 067-1 (or EN 933-5). From these results, an analysis of the alteration of silica bricks in coke ovens in function of the operation time, oven zone and brick side was accomplished.